Pengaruh Prosedur Reviu, Kompetensi, dan Jangka Waktu Pelaksanaan Terhadap Kualiats Reviu Laporan Keuangan Pemerintah Daerah Pada Inspektorat seProvinsi Gorontalo - Deda, Anita; Karamoy, Herman; Gamaliel, Hendrik (Universitas Sam Ratulangi, 2017)
Abstract. This study aims to test the influence of the procedure of the review, the competence of the human resources and the implementation period on the quality of the review of the Financial Statements of the Local Government (LKPD) reported to the Inspectorate in the Province of Gorontalo. The data used in this study are primary data which were collected by using questionnaires as the research instrument and then processed by using SPSS. The data were collected from 92 respondents who are the reviewers and have reviewed the Financial Statements of the Local Government. The method used for this research was quantitative with multiple linear regression analysis. The F-test and t-test were used to test the hypothesis simultaneously and partially. The results show that the variables namely the procedure of the review, the competence of the reviewers and the implementation period altogether affect the quality of the review of the Financial Statements of the Local Government. On the other hand, the procedure of the review in partial has no positive and significant influence on the quality of the review. Thus, it can be concluded that the higher understanding of the procedure of the review, the better quality of the review of the Financial Statements of the Local Government. Then, the competence of the human resources has positive and significant influence on the quality of the review as the higher competence of the human resources of the Inspectorate in the Province of Gorontalo, the better quality of the review of the Financial Statements of the Local Governments. In addition, the implementation period has positive and significant effect on the quality of the review since the better quality of the Financial Statement of the Local Government results from the more effective time and budget allocated for the implementation period done by the staff of the inspectorate in the local government. KeywordsÂ : The Procedure of the Review, Competence, Implementation Period, the Quality of the Review. Abstrak. Penelitian ini bertujuan untuk menguji pengaruh prosedur reviu, kompetensi, dan jangka waktu pelaksanaan terhadap kualitas reviu Laporan Keuangan Pemerintah Daerah pada Inspektorat se Provinsi Gorontalo. Data yang digunakan untuk penelitian ini merupakan data primer yang dikumpulkan menggunakan kuesioner sebagai instrumen penelitian dan diolah dengan program SPSS. Data dikumpulkan dari 92 responden yang merupakan aparat pengawas dan yang pernah melakukan reviu Laporan Keuangan Pemerintah Daerah. Metode yang digunakan yaitu kuantitatif dengan analisis regresi linear berganda. Untuk menguji hipotesis secara simultan dan parsial digunakan Uji F dan Uji t. Hasil penelitian menunjukkan bahwa secara simultan variabel prosedur reviu,Â kompetensi dan jangka waktu pelaksanaan berpengaruh terhadap kualitas reviu Laporan Keuangan Pemerintah Daerah, namun secara parsial, prosedur reviu tidak berpengaruh positif dan signifikan terhadap kualitas reviu Laporan Keuangan Pemerintah Daerah, sehingga dapat disimpulkan bahwa jika pemahaman aparat pengawas terhadap prosedur reviu Laporan Keuangan Pemerintah Daerah lebih maksimal maka kualitas reviu Laporan Keuangan Pemerintah Daerah lebih baik pula. Kompetensi berpengaruh positif dan signifikan, maka semakin tinggi kompetensi sumber daya aparat pengawas yang ada di Inspektorat se Provinsi Gorontalo maka kualitas reviu Laporan Keuangan Pemerintah Daerah akan semakin baik, jangka waktu pelaksanaan berpengaruh positif dan signifikan maka semakin efektif jumlah dan anggaran waktu yang diberikan maka pelaksanaan reviu yang dilakukan oleh aparat pengawas di Inpektorat Daerah akan semakin maksimal, sehingga kualitas reviu Laporan Keuangan Pemerintah Daerah yang dihasilkan akan semakin baik pula. Kata Kunci : Prosedur Reviu, Kompetensi, Jangka Waktu Pelaksanaan terhadap Kualitas Reviu.